A stable europium metal–organic framework as a dual-functional luminescent sensor for quantitatively detecting temperature and humidity. Issue 46 (10th November 2016) - Wang, Dongbo; Tan, Qinghua; Liu, Jingjuan; Liu, Zhiliang
Abstract : A dual-functional Eu-MOF sensor for quantitatively detecting temperature and humidity. Abstract : We report a luminescent Eu metal–organic framework (MOF) with a one-dimensional, open channel filled with water molecule assemblies; this MOF can serve as a dual-functional luminescent sensor for detecting temperature and humidity. Using this MOF, we have developed a self-calibrating ratiometric thermometer that operates within the cryogenic temperature range and simultaneously functions as a luminescent humidity sensor within the relative humidity (RH) range from 33.0% to 85.1%.